Leadership Advancing Great Leaders and Leadership - Crawford, Joseph (Business, Management and Economics, 2023)
The role of a leader has changed drastically since scholars began theorizing about the modern leader. Contemporary society has and is continuing to evolve. Existing leadership theories need to adapt to be relevant to the expectations of leaders now. That is, new leadership theories emerge in their place. This book presents new ideas in leadership in the 21st-century context as well as new models that explain how individuals enact good leadership. This book serves as an opportunity to critique or defend current understandings of leadership and propose new evidence-based and theory-driven insights into leadership. Leadership is understood as more complex than an individual influencing another. Within the broad domains of leadership, there are leaders, followers, leadership processes, followership processes, teams, dyads, relationships, and context. Each of these is critical in defining what it is to be a good leader in increasingly complex professional and personal environments. This book will encourage authors to make compelling arguments not for how leadership is and has been but rather for how good leadership should be.